1978
DOI: 10.1021/jm00210a014
|View full text |Cite
|
Sign up to set email alerts
|

(exo,exo)-2-Aryltropane-3-carboxylic esters, hypoglycemic agents with accompanying analgesic activity

Abstract: (exo, exo)-2-Aryltropane-3-carboxylic esters of types 6, 7, and 10 lower circulating blood glucose levels by 60--80%. This activity is accompanied by an analgesic activity roughly equal to that of codeine. Both of these activities reside in the 1R enantiomer and extensive structure-activity studies failed to separate them. The specific opioid antagonist nalorphine blocks the analgesic activity but does not diminish the hypoglycemic action. Conformational integrity afforded by the ethylene bridge is neccessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Preparative plate chromatography was done with a 1-1.5-mm thick layer of Brinckmann PF 254 silica gel on 20 X 40-cm glass plates. (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparative plate chromatography was done with a 1-1.5-mm thick layer of Brinckmann PF 254 silica gel on 20 X 40-cm glass plates. (3).…”
Section: Methodsmentioning
confidence: 99%
“…The product was extracted with 35,25, and 25 mL of ice cold 2 N hydrochloric acid and each extract was washed quickly with Et20 and drained into a single flask containing 15 mL of concentrated NH4OH and 15 g of ice. Et20 extraction of the liberated base gave 27.4 g (100%) of oily 3 which was about 95% pure by TLC (silica, 3:97 ¡'-PrNH2-Et20'). The NMR spectrum was not definitive but contained no adverse characteristics.…”
Section: Reaction Of Tropane La With Diethylmentioning
confidence: 99%
“…Another well-known phenyltropane analogue is dichloropane, a strong serotonin–norepinephrine–dopamine reuptake inhibitor (SNDRI), which showed during in vivo studies cocaine-like discriminative stimulus effects in the rat . Clarke et al reported a few decades ago the synthesis of a series of 2-aryl tropanes, compounds that have been scarcely described to date. Among them, compound 1a (Figure ) was found to be a narcotic antagonist while 1b was shown to lower circulating blood glucose levels by 60–80% and possesses an analgesic activity similar to codeine.…”
Section: Introductionmentioning
confidence: 99%
“…Some hypoglycemic and analgesic activity associated with the 3-exo esters of this series is described separately in an accompanying paper. 2 There is difficulty inherent in representing R and S enantiomers with a single general formula. The hypoglycemic esters referred to in the previous paragraph have the 1R configuration as drawn in 2, whereas the active narcotic antagonists reported in the present paper have a IS configuration (opposite that of 2).…”
mentioning
confidence: 99%